Metabolic protection by the dietary flavonoid 7,8-dihydroxyflavone requires an intact gut microbiome - Sharma, Priyanka; Silva, Camila; Pfreundschuh, Sarah; Ye, Hong; Sampath, Harini (Frontiers in Nutrition, 2022)
Background 7,8-dihydroxyflavone (DHF) is a naturally occurring flavonoid found in Godmania, Tridax, and Primula species that confers protection against high-fat diet (HFD) induced metabolic pathologies selectively in female mice. We have previously reported that this metabolic protection is associated with early and stable remodeling of the intestinal microbiome, evident in female but not male DHF-supplemented mice. Early changes in the gut microbiome in female DHF-fed mice were highly predictive of subsequent metabolic protection, suggesting a causative association between the gut microbiome and the metabolic effects of DHF. Objective To investigate a causal association between the gut microbiome and the metabolic effects of DHF using a model of antibiotic-induced gut microbiome ablation. Materials and methods Age-matched male and female C57Bl6/J mice were given ad libitum access to HFD and drinking water containing vehicle or DHF for 12 weeks. For antibiotic (Abx) treatment, female mice were given drinking water containing a cocktail of antibiotics for 2 weeks prior to HFD feeding and throughout the feeding period. Metabolic phenotyping consisted of longitudinal assessments of body weights, body composition, food, and water intake, as well as measurement of energy expenditure, glucose tolerance, and plasma and hepatic lipids. Protein markers mediating the cellular effects of DHF were assessed in brown adipose tissue (BAT) and skeletal muscle. Results Metabolic protection conferred by DHF in female HFD-fed mice was only apparent in the presence of an intact gut microbiome. Abx-treated mice were not protected from HFD-induced obesity by DHF administration. Further, tissue activation of the tropomyosin-related kinase receptor B (TrkB) receptor, which has been attributed to the biological activity of DHF, was lost upon gut microbiome ablation, indicating a requirement for microbial “activation” of DHF for its systemic effects. In addition, we report for the first time that DHF supplementation significantly activates TrkB in BAT of female, but not male, mice uncovering a novel target tissue of DHF. DHF supplementation also increased uncoupling protein 1 (UCP1) and AMP-activated protein kinase (AMPK) protein in BAT, consistent with protection from diet-induced obesity. Conclusion These results establish for the first time a requirement for the gut microbiome in mediating the metabolic effects of DHF in female mice and uncover a novel target tissue that may mediate these sexually-dimorphic protective effects.